PENERAPAN INOVASI TEKNOLOGI LUBANG RESAPAN BIOPORI UNTUK MENJAGA EKOSISTEM TANAH DAERAH RAWAN BANJIR DI BANJAR WIRASATYA, DENPASAR SELATAN - Tatiek Kusmawati; Tati Budi Kusmiyarti; M.Tri Gunasih; I B. P. Bhayunagiri; K.Dharma Susila; N. W. Sri Sutari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2012)
Our planet is heating up. We need to do something to avoid a total collapse of environment and our life. The climate changes, have been felt by us in Indonesia, and also happened in the earth side of the world. The effect has come continuously with uncertain time and spread all over the Indonesian territory along 2006 up to 2007 only.The real fact that often meet in our general society, no matter with what that happen around us, the most important thing is we can do some activities as usual, and can buy everything that we want and feel fresh, that all. We also often forget the disaster happening quickly. The global climate changest caused by global warming requires us to change life`s habit that does not care to avoid the rate of global warming. It can be done by illumination and training activities to improve the understanding of that condition and also develop the awareness of the society, especially to introduce Biopori Leach Holes technology done in Banjar Wirasatya Suwung Sidakarya. Biopori leach holes are appropriate technology and environmentally friendly way to cope with flooding (1) improve water infiltration, (2)convert organic waste into compost and reduce emissions of greenhouse gases (CO2 and methane), and (3) utilize the role of activity soil fauna and plant roots, and overcome the problems caused by inactive water such as dengue fever and malaria.